Financing Energy Efficiency, Part 2 : Credit Lines - Wu, Yun; Singh, Jas; Tucker, Dylan Karl (World Bank, Washington, DC, 2018)
Despite offering huge economic returns, implementing energy efficiency measures encounters widespread and systemic barriers. A variety of market failures are keeping project developers from accessing commercial financing for energy efficiency investments. Energy efficiency credit lines are created when international donors loan funds to financial institutions, which then lend to project developers. Credit lines offer a solution where domestic banks are strong but not lending to energy efficiency projects. These lines of credit offer access to finance in the near term, while paving the way for commercial financing in the medium to long term, particularly in the industrial sector. The World Bank's portfolio reveals that under the right conditions, credit lines can achieve dramatic results.